SRCIN1 promotes thyroid carcinoma growth by activating Wnt signaling pathway - Chunyao Han (Scientific Reports)
Abstract The adaptor protein SRCIN1 is a novel Src-binding protein that regulates Src activation through C-terminal Src kinase. SRCIN1 has been shown to promote the development of colorectal cancer, while acting as a tumor suppressor in breast cancer. However, its role in the development of thyroid cancer has remained unknown. In this study, we analyzed the biological characteristics of SRCIN1 in thyroid cancer using public data (HPA, TIMER, GEPIA and UALCAN). Additionally, we investigated the biological impact of SRCIN1 knockdown and overexpression on thyroid cancer cells both in vitro and in vivo. Our results revealed that the expression of SRCIN1 was higher (more than twice) in thyroid cancer tissues than in normal tissues and was positively correlated with tumor stage (stage1 vs. stage4 p < 0.05). Suppression of SRCIN1 promoted cell apoptosis (at least onefold) and inhibited cell proliferation and migration (at least 50%), whereas overexpression had the opposite effect. Furthermore, our analysis indicated that SRCIN1 activates the Wnt/β-catenin signaling axis, as evidenced by increased levels of β-catenin, DVL2, Cyclin D1, c-Myc, and Axin2. TOP/FOP experiments also revealed that Wnt/β-catenin signaling was activated by SRCIN1. It is noteworthy that the specific knockdown of SRCIN1 results in a reduction of key downstream gene targets within the Wnt/β-catenin axis, and tumors in mice treated with SRCIN1-targeting siRNA exhibit significantly smaller volumes (reduction exceeding 50%). Taken together, our study highlights the clinical and therapeutic relevance of SRCIN1 in thyroid cancer and suggests it as a potential therapeutic target for this disease.